PRAWO PUBLICZNE NA UNIWERSYTECIE STEFANA BATOREGO W WILNIE - Tarkowski, Mikołaj (Zeszyty Prawnicze, 2017)
Public Law at The University of Stefan Batory in Vilnius Summary The Law Faculty and Social Science of University of Stefan Batory was a centre of the science of Vilnius lawyers in the interwar period. Examinations and lectures were run both in the field of the public law, private, as well as of support sciences of the law. The article is devoted to the learning of the public law and his academic teachers. Lectures directed for getting to know such objects as the constitutional, church, criminal, tax and administrative law were run on different ranks of studies (from II till the IV year). Syllabus were made up on the basis of provisions of the law about the academic education. In the period of the interwar period discussions took place about their shape. In them professor Eugeniusz Waśkowski, who proposed the legal specialization in senior years supplemented took the active participation for historical researches concerning the institution from the scope of individual branches of the law. In frames this way constructed among others constitutionalists gave a lecture. Among them professor Wacław Komarnicki participated in scientific trips to West-European cities – particularly to Paris. He also contributed to the development of the learning of the public law with one’s work professors Alfons Parczewski and Bolesław Wilanowski who dealt with the canon law and laid them out together with marital rights. Analysing the contribution of Vilnius lawyers to academic achievements of the Polish learning of the criminal law, it is impossible to forget about examinations conducted by professors Bronisław Wróblewski and Stefan Glaser. B. Wróblewski cooperated closely with a more late professor of the Wrocław University Witold Świda. Next, S. Glaser joined in the discussion about legal-medical aspects of abortion. Among this circle it is needed to mention about professor Mieczysław Gutowski – the editor of the periodical Works of the Seminar from the Finances and the Revenue law and the Statistics. There is also described an academic activity of professor Jerzy Panejko, who was concentrated in examinations on the subject matter of the local government and professional council. The Vilnius legal thought survived throughout the period of the II World War. W. Świda, B. Wilanowski and A. Mycielski were continued lectures in the country. Especially W Komarnicki, W. Sukiennicki, or also S. Glaser began the teaching and scientific work at foreign colleges. They cultivated the Vilnius legal thought given rise to and looked after in the interwar period.